Differences between hemispheres and in saccade latency regarding volleyball athletes and non-athletes during saccadic eye movements: an analysis using EEG - Vicente, Renan; Bittencourt, Juliana; Costa, Élida; Nicoliche, Eduardo; Gongora, Mariana; Di Giacomo, Jessé; Bastos, Victor Hugo; Teixeira, Silmar; Orsini, Marco; Budde, Henning; Cagy, Mauricio; Velasques, Bruna; Ribeiro, Pedro (Arquivos de Neuro-Psiquiatria, 2023)
Background The saccadic eye movement is responsible for providing focus to a visual object of interest to the retina. In sports like volleyball, identifying relevant targets quickly is essential to a masterful performance. The training improves cortical regions underlying saccadic action, enabling more automated processing in athletes.Objective We investigated changes in the latency during the saccadic eye movement and the absolute theta power on the frontal and prefrontal cortices during the execution of the saccadic eye movement task in volleyball athletes and non-athletes. We hypothesized that the saccade latency and theta power would be lower due to training and perceptual-cognitive enhancement in volleyball players.Methods We recruited 30 healthy volunteers: 15 volleyball athletes (11 men and 4 women; mean age: 15.08 ± 1.06 years) and 15 non-athletes (5 men and 10 women; mean age: 18.00 ± 1.46 years). All tasks were performed simultaneously with electroencephalography signal recording.Results The latency of the saccadic eye movement presented a significant difference between the groups; a shorter time was observed among the athletes, associated with the players' superiority in terms of attention level. During the experiment, the athletes observed a decrease in absolute theta power compared to non-athletes on the electrodes of each frontal and prefrontal area.Conclusion In the present study, we observed the behavior of reaction time and absolute theta power in athletes and non-athletes during a saccadic movement task. Our findings corroborate the premise of cognitive improvement, mainly due to the reduction of saccadic latency and lower beta power, validating the neural efficiency hypothesis.
Keywords: Saccades; Athletes; Electroencephalography; Reaction Time